Gasto en desarrollo e inclusión social y su relación con la línea de pobreza en el departamento de Loreto en el periodo 2007 – 2023 - Lopez del Aguila, Jesus Paolo (2025)
This research analyzes the relationship between spending on development and social inclusion and poverty reduction in the department of Loreto, Peru, during the period 2007-2023. Using a quantitative approach and the Spearman evaluation method, data from social programs such as Pensión 65 and JUNTOS are examined to evaluate their impact on indicators of poverty and economic dependency. The results reveal that, although increased social spending initially increases the identification of deprivation, its positive effect on poverty reduction may take time to materialize due to time lags and structural challenges. The need for continuous and coordinated evaluation is highlighted, and the implementation of adaptive policies that consider the socioeconomic and cultural particularities of the region. This research provides a critical evaluation of public policies in Loreto, offering recommendations to improve the effectiveness of social spending and promote inclusive development. The findings are relevant for designing future interventions that address the root causes of poverty and strengthen social and economic equity in vulnerable regions.